2022
DOI: 10.1021/acsanm.2c00599
|View full text |Cite
|
Sign up to set email alerts
|

Defect Compensation in Nitrogen-Doped β-Ga2O3 Nanowires: Implications for Bipolar Nanoscale Devices

Abstract: Nitrogen (N) is a promising candidate currently being pursued for p-type doping in Ga2O3. In this work, the results of detailed investigations into N-doped β-Ga2O3 nanowires using microstructural, chemical, and optical analyses are described. Monoclinic β-Ga2O3 nanowires are grown by chemical vapor deposition using a metallic gallium (Ga) precursor and subsequently doped with N by remote plasma by exploiting their nanoscale cross sections and large surface-to-volume ratios. The N incorporation into β-Ga2O3 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, the formation energies of oxygen vacancies are much lower than that of interstitial Ga, so the donor electrons are mainly offered by oxygen vacancies. The acceptors may originate from Ga vacancies (V Ga 2– ) or gallium–oxygen vacancy pairs ((V Ga + V o ) 1– ). , According to the previous reports, the appearance of green bands may also be a result of DAP recombination, , which is due to the recombination of electrons trapped by oxygen vacancies and holes captured by neutral oxygen interstitial defects (O i ) with a slight contribution of V Ga 2– . , The transition processes mentioned above are visualized in the inset of Figure a.…”
Section: Resultsmentioning
confidence: 87%
“…However, the formation energies of oxygen vacancies are much lower than that of interstitial Ga, so the donor electrons are mainly offered by oxygen vacancies. The acceptors may originate from Ga vacancies (V Ga 2– ) or gallium–oxygen vacancy pairs ((V Ga + V o ) 1– ). , According to the previous reports, the appearance of green bands may also be a result of DAP recombination, , which is due to the recombination of electrons trapped by oxygen vacancies and holes captured by neutral oxygen interstitial defects (O i ) with a slight contribution of V Ga 2– . , The transition processes mentioned above are visualized in the inset of Figure a.…”
Section: Resultsmentioning
confidence: 87%
“…The BL and UVL bands have been widely reported in Ga 2 O 3 thin films, in which the BL band (2.9 eV, 430 nm) is attributed to V o or the ( V o , V Ga ) vacancy pair. In addition, the UVL band can be further divided into two components. , Wang et al reported that the UVL bands at 3.4 eV (350 nm) and UV′L at 3.1 eV (400 nm) were caused by the STHs and V o , respectively . Therefore, the Ga 2 O 3 spectra were fitted by the Gaussian peak, which can be deconvoluted into UVL, UV′L, and BL components with the positions of E UV = 3.40 ± 0.05 eV, E UV′ = 3.10 ± 0.05 eV, and E B = 2.90 ± 0.05 eV, respectively. , The results show that the intensity of the UVL band decreases significantly, while that of UV′L and BL changes weakly, as shown in Figure a–d.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the similar ionic radii of Ga 3+ (0.062 nm) and Zn 2+ (0.074 nm), Zn alloying/doping has been widely used to improve the performance of Ga 2 O 3 , [31][32][33][34][35] and some results show that the oxygen vacancy defects can be significantly suppressed by introducing Zn into Ga 2 O 3 . 36,37 However, most previously studies have focused on the most stable b-Ga 2 O 3 , while relatively few studies have been conducted on other metastable phases; 38,39 in particular, Zn-doped e-Ga 2 O 3 has still not been reported.…”
Section: Introductionmentioning
confidence: 99%